Winning habits : 4 secrets that will change the rest of your life - Lyles, Richard I. (Pearson Prentice Hall, 2004)
"Winning Habits is about making great things happen around you ... and for you. This powerful parable identifies the four fundamental habits that lead to success ... and helps you apply those habits in your life ... your whole life ... starting right now." "When it comes to identifying simple personal changes that lead to powerful results, nobody knows more than Dick Lyles. And nobody's better at helping you make those changes stick - for today, tomorrow, and the rest of your life. (If you're among the millions who've been touched by his personal appearances and consulting engagements, you already know that!)" "Whether you're struggling to jump start your career ... or lead a team to greatness ... or improve your entire organization's performance ... or you're a consultant, coach, or trainer ... Winning Habits has the answers. Read it. Share it. Live it!"--Jacket.